Washington 101 : An Introduction to the Nation's Capital - Green, Matthew N.; Yarwood, Julie; Daughtery, Laura; Mazzenga, Maria; SpringerLink (Online service). (New York : Palgrave Macmillan US, 2014)
Washington 101 offers a layman's introduction to the richness and diversity of the nation's capital. An exploration of the history, politics, architecture, and people of the city and region, Washington 101 is a must-read for anyone curious to learn more about Washington.
Keywords: Environment; Political science; World politics; Europe -- Politics and government; Urban geography; Urban planning; City planning; Environmental management